Routine immunization of adults by pharmacists: Attitudes and beliefs of the Canadian public and health care providers - MacDougall, D. (Hum Vaccin Immunother, 2016)
Vaccine coverage among adults for recommended vaccines is generally low. In Canada and the US, pharmacists are increasingly becoming involved in the administration of vaccines to adults. This study measured the knowledge, attitudes, beliefs, and behaviors of Canadian adults and health care providers regarding pharmacists as immunizers. Geographically representative samples of Canadian adults (n = 4023) and health care providers (n = 1167) were surveyed, and 8 focus groups each were conducted nationwide with adults and health care providers. Provision of vaccines by pharmacists was supported by 64.6% of the public, 82.3% of pharmacists, 57.4% of nurses, and 38.9% of physicians; 45.7% of physicians opposed pharmacist-delivered vaccination. Pharmacists were considered a trusted source of vaccination information by 75.0% of the public, exceeding public health officials (68.3%) and exceeded only by doctors and nurses (89.2%). Public concerns about vaccination in pharmacies centered on safety (management of adverse events), record keeping (ensuring their family physician was informed), and cost (should be no more expensive than vaccination at public health or physicians' offices). Concerns about the logistics of vaccination delivery were expressed more frequently in regions where pharmacists were not yet immunizing than in jurisdictions with existing pharmacist vaccination programs. These results suggest that the expansion of pharmacists' scope of practice to include delivery of adult vaccinations is generally accepted by Canadian health care providers and the public. Acceptance of this expanded scope of pharmacist practice may contribute to improvements in vaccine coverage rates by improving vaccine accessibility.